Identification of bacterial isolates in urinary tract infections patients of Basrah province - Eidan, Zainab Ali; Shani, Wafaa S.; Almazini, Muna Abdul-Imam (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Urinary tract infections (UTIs) are among the most common bacterial diseases worldwide that are caused primarily by members of the Enterobacteriaceae family. This study aimed to identify the most frequent bacterial agents associated with UTIs and analyze their patterns of antibiotic resistance using the Vitek®2 system. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The study included 200 urine samples collected from adult UTI patients of both sexes. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The characterization of bacterial isolates revealed the following distribution: Escherichia coli (35 isolates, 50%), Staphylococcus aureus (18 isolates, 25.7%), Klebsiella pneumoniae (5 isolates, 7.14%), Staphylococcus spp. (4 isolates, 5.7%), Streptococcus spp. (3 isolates, 4.2%), Pseudomonas spp. (3 isolates, 4.2%), and Proteus mirabilis (2 isolates, 2.86%). Antibiotic resistance testing showed that ceftazidime had the highest resistance rate (88.57%), while amikacin had the lowest (17.14%). Additionally, extended-spectrum β-lactamase (ESBL) production was detected in 35 E. coli isolates. Of these, 22 isolates (62.86%) tested positive for ESBL production, while 13 isolates (37.14%) were negative. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. This study concluded that E. coli is the most prevalent bacterial species causing UTIs. Furthermore, the E. coli isolates demonstrated a high capacity for ESBL production, highlighting the need for effective antimicrobial management and monitoring.